Search
Ask a question

Answers by Robert A.

-3xy/6xy is [ (-3xy) / 6] • xy which equals (-1/2)x2y2  not -1/2 and not -2.   So the answer is: ( 48x7y6 ) - ( ( 1/2 ) x2y2 )   PEMDAS   And you perform the M and D in order left to right then the A and S in order left to right. You do not perform all...

Do you mean: ( 3a2x -6ax2 +24a2x2 ) / ( 12a2x2 )   The way you wrote it is: (3a2x) - (6ax2) + ( [ (24a2x2) / 12 ] • a2x2 )   Mathematics is a language; and just like in English, you need to get the subjects, verbs, adjectives, and commas in the right place...

So why did you post the same thing twice in 25 minutes????? That's a no-no on bulletin boards.   This is a physics problem. But if you want to solve it like it was a math problem - okay.   1st you can find the x-axis of symmetry.  x= -b/2aThen you can find ...

For a polynomial of form  Ax^2 + Bx + C = 0 A tells the end behavior.  Negative says it opens down, the end behavior is down on both left and right. The axis of symmetry is given by x = -b/2a Find -b/2a, that is the ex value for the vertex. Plug that value into...

d/dx(x^(1/x))   Express x^(1/x) as a power of e      x^(1/x) = e^(log(x^(1/x))) = e^((log(x))/x)      = d/dx(e^((log(x))/x)) Using the chain rule     d/dx(e^((log(x))/x)) = ( de^u)/( du) ( du)/( dx)   ...

d/dx (log(4) x e^x) Factor out constants:      = log(4) (d/dx(e^x x)) Use the product rule,      d/dx(u v) = v ( du)/( dx) + u ( dv)/( dx),      where u = e^x and v = x:      =...

You have a quadratic in the form of: y = (x-h)^2 + k   1) The vertex is (h,k) or (2,-1) 2) The axis of symmetry is x=h  (or x=2) 3) The a=1/2 widens the parabola and is + so the graph opens up The h = +2 shifts the parabola 2 to the right of the y axis The...

Write two equations.   the difference of the two numbers is 17 X - Y = 17   the larger is twice the smaller decreased by 13 X = 2 ·Y - 13   Now solve the simultaneous equations by any method, substitution or by elimination.

For a parabola in the form y = A(x-h)2 + k  the vertex is (h,k)SO   1) Rewrite the equation in that form. OR Using the x axis of symmetry is -(b/2a)   find x then substitute that into the equation   to get the y value.   x = -(b/2a)...

You gave the method to the solution in your question. Solve by substituting y=3x+4  INTO 7x+2y=21   7x+2y=21 becomes 7x+2(3x+4)=21 distribute 7x+6x+8=21 now solve for x

This problem (a physics problem) requires a little more than just being able to solve a simple math formula. You need to understand what is going on well enough see that if one is going X speed and the other is going Y speed then they are traveling towards each other at a speed of X+Y...